Actions required to implement integrated care for older people in the community using the World Health Organization's ICOPE approach: A global Delphi consensus study - Briggs, Andrew; De Carvalho, I. (Public Library of Science, 2018)
Background: Integrated care is recognised as an important enabler to healthy ageing, yet few countries have managed to sustainably deliver integrated care for older people. We aimed to gather global consensus on the key actions required to realign health and long-term systems and integrate services to implement the World Health Organization (WHO) Integrated Care for Older People (ICOPE) approach. Methods: A two-round eDelphi study, including a global consultation meeting, was undertaken to identify, refine and generate consensus on the actions required across high-, middle- and lowincome countries to implement the WHO ICOPE approach. In round 1, a framework of 31 actions, empirically derived from previous WHO evidence reviews was presented to panellists to judge the relative importance of each action (numeric rating scale; range:1-9) and provide free-text comments concerning the scope of the actions. These outcomes were discussed and debated at the global consultation meeting. In round 2, a revised framework of 19 actions was presented to panellists to measure their extent of agreement and identify 'essential' actions (five-point Likert scale; range: strongly agree to strongly disagree). A threshold of =80% for agree/strongly agree was set a priori for consensus. Results: After round 1 (n = 80 panellists), median scores across 31 actions ranged from 6 to 9. Based on pre-defined category thresholds for median scores, panellists considered 28 actions (90.3%) as 'important' and three (9.7%) as 'uncertain'. Fifteen additional actions were suggested for inclusion based on free-text comments, creating 46 for consideration at the global consultation meeting. In round 2 (n = 84 panellists), agreement (agree or strongly agree) ranged from 84.6-97.6%, suggesting consensus. Fourteen (73.7%) actions were rated as essential. Conclusion: Fourteen essential actions and five important actions are necessary at system (macro; n = 10) and service (meso; n = 9) levels to implement community-based integrated care for older people.